Lower limb kinematics in individuals with chronic low back pain during walking. (April 2020) - Rahimi, Atefeh; Arab, Amir Masoud; Nourbakhsh, Mohammad Reza; Hosseini, Sayed Mohsen; Forghany, Saeed
Abstract: Several investigators have suggested the presence of a link between Chronic Low Back Pain (CLBP) and lower limbs kinematics that can contribute to functional limitations and disability. Moreover, CLBP has been connected to postural and structural asymmetry. Understanding the movement pattern of lower extremities and its asymmetry during walking can provide a basis for examination and rehabilitation in people with CLBP. The present study focuses on lower limbs kinematics in individuals with CLBP during walking. Three-dimensional movements of the pelvic, hip, knee and ankle joints were tracked using a seven-camera Qualysis motion capture system. Functional dada analysis (FDA) was applied for the statistical analysis of pelvic and lower limbs motion patterns in 40 participants (20 CLBP and 20 controls). The CLBP group showed significantly different hip motion pattern in the transvers plane, altered knee and ankle motion pattern in the sagittal plane on the dominant side and different hip motion pattern in the transvers and frontal planes on the non-dominant side in comparison with the control group over the stance phase. In terms of symmetry, in the CLBP group, hip and knee moved through a significantly different motion patterns in the transvers plane on the dominant side in comparison with the non-dominant side. In the control group, knee moved through a significantly different motion pattern in the transvers plane on the dominant side in comparison with the non-dominant side. In conclusion, low back pain lead to altered movement patterns of the main joints of lower limbs especially on the dominant side during stance phase. Therefore, care should be taken to examine dominant lower limb movement pattern in CLBP to make a better clinical decision.